2016
DOI: 10.3171/2015.10.spine15670
|View full text |Cite
|
Sign up to set email alerts
|

Rate of perioperative neurological complications after surgery for cervical spinal cord stimulation

Abstract: OBJECTIVE Cervical spinal cord stimulation (cSCS) is used to treat pain of the cervical region and upper extremities. Case reports and small series have shown a relatively low risk of complication after cSCS, with only a single reported case of perioperative spinal cord injury in the literature. Catastrophic cSCS-associated spinal cord injury remains a concern as a result of underreporting. To aid in preoperative counseling, it is necessary to establish a minimum rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 36 publications
(50 reference statements)
4
7
0
Order By: Relevance
“…Lead migration leading to loss of efficacy, discomfort due to positioning of the leads (positional effect), and device related complications are commonly encountered in patients with upper limb and neck pain. 15-17 , 34 , 39 In the current study, only 1 in 45 subjects required an explant (2.2%) and there were no cases of lead migration or other complications despite positioning the leads at C2 vertebral level in all enrolled subjects. More importantly, all the device-related adverse events were manageable and resolved shortly after reprogramming.…”
Section: Discussionmentioning
confidence: 53%
“…Lead migration leading to loss of efficacy, discomfort due to positioning of the leads (positional effect), and device related complications are commonly encountered in patients with upper limb and neck pain. 15-17 , 34 , 39 In the current study, only 1 in 45 subjects required an explant (2.2%) and there were no cases of lead migration or other complications despite positioning the leads at C2 vertebral level in all enrolled subjects. More importantly, all the device-related adverse events were manageable and resolved shortly after reprogramming.…”
Section: Discussionmentioning
confidence: 53%
“…This notion may be reflected in the study by Al-Kaisy et al [ 18 ], where 10 kHz SCS devices were significantly less likely to be explanted relative to traditional stimulation [ 28 ]. Additionally, another potential concern with cervical SCS is the occurrence of neurological complications due to the complex anatomy surrounding the cervical spine [ 7 , 10 ]. None of the studies included in this review reported occurrence of neurological complications, indicating that such risks are minimal with 10 kHz SCS.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulating the spinal cord through electrical impulses can create a neuromodulatory effect on the nervous system and can change the perception of pain in some patients [3,4]. Although traditional SCS has been used in practice for decades for chronic back and leg pain, favorable clinical results are becoming increasingly apparent for cervical SCS systems [3,[6][7][8][9][10][11]. The Neuromodulation Appropriateness Consensus Committee (NACC) recommends cervical SCS for the treatment of upper extremity pain since it is a safe, minimally invasive, and reversible procedure [12].…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] Lead migration is among the most concerning complications reported in prospective studies of cervical lead placement for management of pain. 7,[24][25][26][27] A systematic literature review of outcomes in patients with cervical SCS documented the rates for hardware malfunction (17.8%), lead migration (13.9%), lead fracture (6.7%), pain over implant site (4.4%) and infection (2.2%). 28 The AE rates reported in this study and in the previous studies evaluating 10 kHz SCS for upper limb and neck pain treatment compare favorably with the published literature…”
Section: Discussionmentioning
confidence: 99%